تقييم تأثير دقة التمييز الهندسية للصور على نوعية النموذج ثلاثي الأبعاد في المساحة التصويرية القريبة المؤتمتة - الخليل عمر; فحصة إياد (Latakia University Journal -Engineering Sciences Series, 2018)
إن الهدف الرئيسي لهذا البحث هو دراسة تأثير دقة التمييز الهندسية للصور فقط على النوعية الهندسية للنموذج ثلاثي الأبعاد المحسوب منها. تم في هذا البحث تثبيت كل العناصر التي تؤثر على نوعية النموذج وتغيير دقة التمييز فقط للصور المستخدمة. يعتبر عدد الصور الملتقطة للعنصر، عدد نقاط الضبط وتوزعها ودقتها، آلة التصوير المستخدمة وكونها معايرة أم لا، من أهم العوامل المؤثرة على عملية النمذجة. لتحييد تأثير العوامل الداخلية لآلة التصوير المستخدمة في التقاط الصور، قمنا بعملية معايرة لهذه الآلة، كما حرصنا على التخطيط المسبق لعملية التصوير وذلك لتفادي المشاكل الناتجة عن نقص أو زيادة عدد الصور والتي تؤثر بشكل مباشر على نوعية النموذج وكماليته. ومن ناحية أخرى، تم استخدام معطيات ضبط دقيقة تم الحصول عليها من أعمال مساحية دقيقة (شبكة جيوديزية أفقية وشبكة تسوية). في هذه الدراسة سنختبر تأثير دقة تمييز الصور فقط على توليد غمامة كثيفة من النقاط بتطبيق طريقة البنية انطلاقاً من الحركة Structure from Motion (SfM) واستنتاج النموذج السطوحي منها والصورة المصححة عامودياً لواجهة من واجهات منشأ في جامعة تشرين. The main objective of this research is to study the effect of the accuracy of images’ geometric resolution only on the geometric quality of the resulted three-dimensional model. In this research, all factors that affect the quality of the model are fixed and the geometric resolution is changed only for the used images. The number of captured images, the number and the distribution and the accuracy of control points, the camera being used and whether or not it is calibrated, are among the most important factors influencing the modeling process. In order to neutralize the effect of the inner parameters of the used camera, a process of calibration was achieved. On the other hand, we have pre-planned the process of photography to avoid problems resulting from the lack or increase the number of images, that directly affect the quality and completeness of the model. In addition, accurate control data obtained from precise survey work (horizontal geodetic network and leveling network) was applied. In this study, we examined the effect of image resolution on the generation of a dense cloud of points by applying the Structure from Motion (SfM) and deducing the surface model and the orthophoto of a facade of a building at Tishreen University.